Metabolic phenotype-microRNA data fusion analysis of the systemic consequences of Roux-en-Y gastric bypass surgery - Wu, Q; Li, J V; Seyfried, F; le Roux, C W; Ashrafian, H; Athanasiou, T; Fenske, W; Darzi, A; Nicholson, J K; Holmes, E; Gooderham, N J (International Journal of Obesity, 2015)
Background/Objectives: Bariatric surgery offers sustained marked weight loss and often remission of type 2 diabetes, yet the mechanisms of establishment of these health benefits are not clear. Subjects/Methods: We mapped the coordinated systemic responses of gut hormones, the circulating miRNAome and the metabolome in a rat model of Roux-en-Y gastric bypass (RYGB) surgery. Results: The response of circulating microRNAs (miRNAs) to RYGB was striking and selective. Analysis of 14 significantly altered circulating miRNAs within a pathway context was suggestive of modulation of signaling pathways including G protein signaling, neurodegeneration, inflammation, and growth and apoptosis responses. Concomitant alterations in the metabolome indicated increased glucose transport, accelerated glycolysis and inhibited gluconeogenesis in the liver. Of particular significance, we show significantly decreased circulating miRNA-122 levels and a more modest decline in hepatic levels, following surgery. In mechanistic studies, manipulation of miRNA-122 levels in a cell model induced changes in the activity of key enzymes involved in hepatic energy metabolism, glucose transport, glycolysis, tricarboxylic acid cycle, pentose phosphate shunt, fatty-acid oxidation and gluconeogenesis, consistent with the findings of the in vivo surgery-mediated responses, indicating the powerful homeostatic activity of the miRNAs. Conclusions: The close association between energy metabolism, neuronal signaling and gut microbial metabolites derived from the circulating miRNA, plasma, urine and liver metabolite and gut hormone correlations further supports an enhanced gut-brain signaling, which we suggest is hormonally mediated by both traditional gut hormones and miRNAs. This transomic approach to map the crosstalk between the circulating miRNAome and metabolome offers opportunities to understand complex systems biology within a disease and interventional treatment setting.